Unlock knowledge potential from management consulting - Lopes da Costa, R.; Pereira, L.; Dias, Á.; Gonçalves, R. (International Journal of Learning and Intellectual Capital, 2022)
Management consulting area is a worldwide phenomenon of business increase over time. However, the subject field is poorly supported by academic research. There’s a lot of knowledge that comes up every day from companies’ transformations and performance improvement and business models changed. The research was done in a form of semi-structured interviews and questionnaires applied to management consultants and SME managers in Portugal, and it has shown that competency comes from different knowledge domains in business such as know, know-how and know-to be, making important to have processes to unlocked their knowledge to organisations and to the society.